Impact of Šventoji port jetties on coastal dynamics of the Baltic sea - Kriaučiūnienė, Jūratė; Žilinskas, Gintautas; Pupienis, Donatas; Jarmalavičius, Darius; Gailiušis, Brunonas (Journal of Environmental Engineering and Landscape Management, 2013)
As the safe depth for navigation is no longer ensured due to intense accumulation of sediments in the avanport of the old port, which was constructed in 1923–1940, reconstruction of Šventoji port jetties was planned, which should commence in 2013. The assessment of impact of Šventoji port jetties was done on the nearby coasts, based on analysis of the 20th and 21st century cartographic material as well as monitoring data on coastal dynamics. The old port construction caused the formation of the accumulative cape; the area of which has grown to 44.90 ha. The coastline erosion processes have become especially intense northwards from the formed cape to the Latvian border. Approx. 38.41 ha area of land has been washed-out in the section. During the last 17 years, the southern jetty has become more and more pervious to sediments. Sediment volume stabilization occurred on the northern side of the jetty, and accumulation tendency was in the southern part of the port. Results of sediment transport modelling with MIKE 21 confirm that the reconstruction of Šventoji port according to alternative “1” (length of jetties – 400 m) answers the minimal requirements of port and makes the least impact for the hydrodynamic and lithodynamic processes in the Baltic Sea nearshore. The reconstruction of port according to alternative “2” (length of jetties – 800 m) will cause the intensive changes of the Baltic Sea coastline dynamics in adjacent regions. First published online: 14 Dec 2012